(untitled) (Research, Society and Development, 2020)
Dental implants performed immediately after tooth extraction have a high success rate and allow the rehabilitation of the patient with less interventions to finalize the case. The study in question aims to report a case of a patient who underwent the immediate implantation technique in the aesthetic area. In this article, a clinical case of a young female patient is reported, in which there was an indication of extraction of the element 11, right central incisor, and after the atraumatic extraction, the dental implant was installed immediately, however, without load immediate. Geistlich Bio-Oss® bone graft was used to fill the spaces between the implant and the socket and to improve the quality of soft tissues, concomitant connective tissue grafting was performed. The patient’s provisional rehabilitation consisted of installing an adhesive prosthesis, which allows for temporary rehabilitation, without placing a load on the newly installed implant and without wearing on adjacent teeth. It is known that the aesthetics of the smile has a direct impact on the patient’s self-esteem, since human beings are social beings who base their entire existence on communication and image, having a prominent part of the face negatively affected can bring enormous losses to self-esteem and psychosocial relationships. Thus, the use of this technique enabled the patient’s rehabilitation in a functional and aesthetic way, having gained in her quality of life.